Adherence to medication, glycaemic control and hospital attendance in young adults with type 2 diabetes. Issue 6 (12th June 2018) - Kunasegaran, Shalini; Beig, Junaid; Khanolkar, Manish; Cundy, Tim
Abstract: Type 2 diabetes is becoming common among people in their 20s and 30s. Glycaemic control is suboptimal in this group and is associated with poor medication adherence. We studied medication adherence over a 24‐month period in all diabetes clinic registrants ( n = 266) between the ages of 18 and 39 years. We reviewed their glycaemic control using mean HbA1c over the study period and examined hospital records to determine the number of hospital attendances during this time. We found that less than half the group (47%) had good adherence (>90%) and 21% of the group had very poor adherence (<50%). Mean adherence was slightly poorer in women compared to men (73% vs 76%, P = 0.04). There was a marked inverse relationship between adherence and glycaemic control. Mean HbA1c is 70 mmol/mol among those with good adherence and mean HbA1c is 97 mmol/mol among those with very poor adherence ( P < 0.05). Fifty‐seven per cent of the study group had at least one hospital attendance during this time. Eighty‐eight hospital attendances were due to a medical cause. Study of trend showed more medical admissions among those with very poor adherence ( P = 0.03). Mean HbA1c was higher in those who required medical admissions (87 mmol/mol vs 75 mmol/mol) when compared to those with no hospital attendance. Our study shows that poor adherence is common and significantly related to glycaemic control as well as unplanned hospital attendances for medical conditions. Despite limitations, our study provides valuable information on medication adherence and its impact on glycaemic control and morbidity among young people with type 2 diabetes.